2017
DOI: 10.1111/dmcn.13540
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrate and clinical significance of general movements: an update

Abstract: General movements are present from early fetal life to 3 to 5 months corrected age. Atypical general movements, especially in the last, so‐called fidgety general movement phase, are predictive of cerebral palsy (CP). This review updates knowledge on the neural substrate and clinical significance of typical and atypical general movements. Typical general movements are primarily characterized by complexity and variation. Presumably these core characteristics are initially induced by modulating activity of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
116
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 49 publications
2
116
0
6
Order By: Relevance
“…Observational GMA defines that infant spontaneous movements have complexity denoted by a flow of changes in the movement direction of the participating body parts and variation across time where the infant explores the movement possibilities that the body offers. These spatial and temporal changes in movements are tightly intertwined [18]. The spatial and temporal changes in these movement features are difficult to represent as a single feature across the entire video recording, as was carried out in a previous study using the standard deviation of the center of motion [12].…”
Section: Study Sample Size 1 Sens (%) Spec (%) Acc (%) Featuresmentioning
confidence: 98%
“…Observational GMA defines that infant spontaneous movements have complexity denoted by a flow of changes in the movement direction of the participating body parts and variation across time where the infant explores the movement possibilities that the body offers. These spatial and temporal changes in movements are tightly intertwined [18]. The spatial and temporal changes in these movement features are difficult to represent as a single feature across the entire video recording, as was carried out in a previous study using the standard deviation of the center of motion [12].…”
Section: Study Sample Size 1 Sens (%) Spec (%) Acc (%) Featuresmentioning
confidence: 98%
“…The first year after conception is characterised by high developmental activity in the brain, especially in the cortical subplate and cerebellum. As the complexity and variation of GMs emergence and the synaptic activity in the cortical subplate emergence coincide, Hadders-Alga speculated that the cortical subplate is the neural substrate of GMs complexity and variation [27]. The subplate is a transient structure that gradually dissolves between 3 months before term and 3 months' corrected age, when the cortical plate takes over.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that predictive validity of the General Movements Assessment (GMA) for CP is better in infants born preterm than those born at term. 2,3 This is best illustrated by the forest plots in the supplementary material of the paper by Kwong et al, particularly by the studies with the least bias. Presumably this difference in predictive validity is brought about by the difference in the type of lesions of the brain.…”
mentioning
confidence: 98%
“…At early fetal stage the neural substrate of general movements is the cortical subplate; in the third trimester of gestation the cortical subplate starts to dissolve and its function is gradually taken over by the cortical plate (which increases in size). 2 The efferent connections of both cortical subplate and cortical plate run through the periventricular white matter. In the studies that used the Hadders-Algra GMA, the proportion assessing outcome in infants born at term was larger than those that used the Prechtl GMA; while the proportion of studies consisting entirely of infants born preterm that used the Hadders-Algra method was smaller than those that used the Prechtl method.…”
mentioning
confidence: 99%
See 1 more Smart Citation